Application of the Least Squares Solutions in Image Deblurring. (24th February 2015) - Stanimirović, Predrag S.; Stojanović, Igor; Katsikis, Vasilios N.; Pappas, Dimitrios; Zdravev, Zoran
Abstract : A new method for the reconstruction of blurred digital images damaged by separable motion blur is established. The main attribute of the method is based on multiple applications of the least squares solutions of certain matrix equations which define the separable motion blur in conjunction with known image deconvolution techniques. The key feature of the proposed algorithms is reflected in the fact that they can be used only in symbiosis with other image restoration algorithms.